Persepsi Nasabah Terhadap Kualitas Pelayanan Produk Giro Berkah Wadi’ah Di Bank Syariah Nasional Cabang Bengkulu - Tina Azzanii; Desi Isnaini; Uswatun Hasanah (Prodi Ekonomi Syariah Universitas Majalengka, 2026)
Abstract: This study examines customer perceptions of service quality in the Giro Berkah Wadi’ah product at Bank Syariah Nasional Bengkulu Branch. This issue is important because Islamic banking services are not assessed only through product compliance with sharia principles, but also through customers’ direct experiences of accuracy, responsiveness, assurance, empathy, and physical service facilities. Previous studies have generally discussed Islamic bank service quality, customer satisfaction, or wadi’ah savings products, while product-specific studies on giro wadi’ah at branch level remain limited. Therefore, this study formulates two problems: how the Giro Berkah Wadi’ah service is implemented and how customers perceive its service quality. This research uses a descriptive qualitative type and approach, located at Bank Syariah Nasional Bengkulu Branch. Data were obtained through in-depth interviews, direct observation, and documentation involving ten active Giro Berkah Wadi’ah customers and two frontliner employees selected by purposive sampling. Data were analyzed through reduction, data display, conclusion drawing, and verification using SERVQUAL and the Tri-Component Attitude Model. The study finds that customers generally perceive reliability, responsiveness, assurance, and empathy positively, while tangibles still require improvement. It recommends strengthening physical facilities, service consistency, and sharia-based product communication.